Role of local anaesthetic nerve block in endoscopic sinus surgery: A systematic review and meta‐analysis. (5th June 2018) - Shamil, E.; Rouhani, M.J.; Basetti, S.; Bast, F.; Hopkins, C.; Surda, P.
Abstract : Objective: The aim of the study was to perform a systematic review of existing evidence on the role of local anaesthetic nerve block (LAB) in patients undergoing endoscopic sinus surgery (ESS). Design: The databases searched were the Cochrane Register of Controlled Trials, MEDLINE and Embase using the Ovid portal (1946‐2017). Results: Seven randomised controlled trials were included. Due to considerable heterogeneity of data, only two studies were pooled into meta‐analysis which demonstrated a statistically significantly better surgical field quality during ESS in the LAB group compared with the control group (MD −0.86; 95% CI −2.24, 0.51; P  = .009). No adverse events related to LAB toxicity were reported. Conclusions: Sphenopalatine ganglion LAB with adrenaline carries relatively low risk of morbidity, but may improve the quality of the surgical field in terms of bleeding. However, there are limitations of the study due to heterogeneity of methods, quality and size of the studies. Well‐conducted large RCTs are needed using standardised inclusion criteria, balanced baseline characteristics of cohorts, and validated subjective and objective outcome measures.